Effects of and preference for student‐ and teacher‐implemented good behavior game in early elementary classes. Issue 1 (7th November 2022) - Peltier, William; Newell, Kristen L.; Linton, Elizabeth; Holmes, Sarah C.; Donaldson, Jeanne M.
Abstract : Disruptive behavior during instruction is a common problem in elementary classrooms. One intervention to reduce disruptive behavior is the Good Behavior Game (GBG). In this study, the students of 2 early elementary classrooms experienced 3 versions of the GBG: experimenter‐implemented, teacher‐implemented, and student‐implemented. The effects of the GBG on disruptive behavior and peer interactions were evaluated using a combined reversal and multielement design. Student preference for conditions was assessed via a group arrangement of a concurrent‐chains preference assessment. All versions of the game reduced disruptive behavior compared to baseline, but the rate of disruptive behavior was slightly higher during the teacher‐implemented sessions in Class 1. Few peer interactions occurred during the game; however, negative interactions increased slightly in both classes during the GBG. Students overwhelmingly preferred the student‐implemented version of the game. This study provides support for student implementation of the GBG and offers an approach to student shared governance in the classroom.